The use of bibliometric indicators to help peer-review assessment - Haeffner-Cavaillon, Nicole (Birkhauser, 2009)
Inserm is the only French public research institution entirely dedicated to human health. Inserm supports research across the biomedical spectrum in all major disease areas, from fundamental lab-based science to clinical trials. To translate its scientists findings into tangible health benefits Inserm has its own affiliated company, Inserm Transfert, which works with industry. Since 2001, Inserm has set up the on-line file management software for the evaluation of researchers and laboratories, called EVA (www.eva.inserm.fr). EVA includes all grant applications, assessment reports, grading evaluation forms and include an automated bibliometric indicator software that enables to calculate for each researcher of the teams, the number of publications, impact factor of journals, number of citations, citation index, number of Top 1% publications … The indicators take into account research fields, the year of publications, the author position within the participants. Bibliometrics is now considered as a tool for science policy providing indicators to measure productivity and scientific quality, thereby supplying a basis for evaluating and orienting R&D. It is also a potential tool for evaluation. It is neutral, allows comparative (national & international) assessment and may select papers in the forefront in all fields. For each team bibliometric indicators were calculated for all researchers with permanent positions or long term positions (3 to 5 years). The use of bibliometric indicators requires a great vigilance but according to our experience they without any doubt enrich the committee’s debates. We present the analysis of the data of 600 research teams evaluated in 2007–2008.